2017
DOI: 10.1038/s41598-017-16430-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic data reveal a loss of diversity in two species of tuco-tucos (genus Ctenomys) following a volcanic eruption

Abstract: Marked reductions in population size can trigger corresponding declines in genetic variation. Understanding the precise genetic consequences of such reductions, however, is often challenging due to the absence of robust pre- and post-reduction datasets. Here, we use heterochronous genomic data from samples obtained before and immediately after the 2011 eruption of the Puyehue-Cordón Caulle volcanic complex in Patagonia to explore the genetic impacts of this event on two parapatric species of rodents, the colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…Collectively, these findings lead us to expect that post-eruption genetic variability in each population should also have been reduced. Analyses of pre- and post-eruption samples from the study species using a genome-wide panel of single nucleotide polymorphisms (SNPs) support this prediction, revealing small but significant decreases in genetic variability in both study populations [28]. These findings indicate that abrupt reductions in population size of the magnitude reported here (25–50%) can produce significant changes in genetic variability over short time scales.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Collectively, these findings lead us to expect that post-eruption genetic variability in each population should also have been reduced. Analyses of pre- and post-eruption samples from the study species using a genome-wide panel of single nucleotide polymorphisms (SNPs) support this prediction, revealing small but significant decreases in genetic variability in both study populations [28]. These findings indicate that abrupt reductions in population size of the magnitude reported here (25–50%) can produce significant changes in genetic variability over short time scales.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies [27, 28] have revealed that the 2011 eruption affected levels of genetic variability in both study species and a primary objective of our analyses was to identify the demographic parameters that may have contributed to these changes in genetic variation. Loss of genetic variability following anthropogenically-induced bottlenecks has been documented for a number of mammalian species, including elephant seals [41], fur seals [42], black-footed ferrets [43], arctic foxes [44], lions [45], and Florida panthers [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with former studies revealing an increased weight of the migration after disturbance that provide opportunities for recruitment (Becheler, Benkara, Moalic, Hily, & Arnaud‐Haond, 2014; Becheler, Diekmann, Hily, Moalic, & Arnaud‐Haond, 2010; Eriksson, 1993; Reusch, 2006). Increase in available open space lead, in some extreme cases, to mosaic patterns where impacted areas colonized by external sources are genetically distinct from the surviving local patches (Parvizi, Craw, & Waters, 2019) or to a reset of the genetic composition (Hsu et al, 2017; Wilmer et al, 2011) after the near‐total crash of populations. The surprising consequences of such profound genetic reset rely in a resulting diversity comparable to the original one, as the rapid recolonization is achieved through intense long‐distance migration (i.e., migration pool model), bringing new migrants and alleles in impacted populations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most studies have focused on the consequences of a catastrophic event on genetic structure by analyzing the impacted populations a posteriori (Jacquemyn, Roldán‐Ruiz, & Honnay, 2010; Russello, Gladyshev, Miquelle, & Caccone, 2004) or sometimes benefitting from banks of ancient data (e.g., data from museum specimens: Nyström, Angerbjörn, & Dalén, 2006; archeological data: Hadly et al, 2004; Weber, Stewart, & Lehman, 2004). Population‐based studies in which information was gathered before and after the extreme event in order to quantify the changes in genetic diversity caused by the catastrophe are rare (but see Gallardo, Köhler, & Araneda, 1995; Hsu et al, 2017; Pujolar et al, 2011; Wilmer et al, 2011). These studies have reported a loss of genetic diversity by directly comparing the standing variation before and after the event.…”
Section: Introductionmentioning
confidence: 99%